A controllable local drug delivery system based on porous fibers for synergistic treatment of melanoma and promoting wound healing. (30th September 2019) - Yuan, Zhipeng; Zhang, Kexin; Jiao, Xiangyu; Cheng, Yaru; Zhang, Yiyi; Zhang, Peixun; Zhang, Xueji; Wen, Yongqiang
Abstract : A controllable local drug delivery system can effectively inhibit melanoma growth with chemo-photothermal synergistic therapy and accelerate wound healing. Abstract : A dual function system that inhibits tumor growth while promoting wound healing is very necessary for melanoma treatment since tumor killing and skin healing are two complementary and influential processes. Herein, a controllable local drug delivery system based on porous fiber membranes incorporated with CuS nanoparticles is designed for chemo-photothermal synergistic melanoma therapy and promoting wound healing. The porous structure on the fiber surface significantly increases the drug loading capacity of the membrane and the photothermal effect of incorporated CuS nanoparticles is used to control the drug release rate. Benefitting from the chemo-photothermal synergistic therapy, the composite membrane can effectively kill melanoma cells in vitro and inhibit tumor growth in vivo . Furthermore, the membrane can also significantly promote the cutaneous wound healing by providing mechanical support and releasing copper ions. Thus, this work provides new ideas for the development of multifunctional local treatment and postoperative care systems.